Anti Viral Medicinal Plants – An Ethnobotanical Approach - K. Manoharan, B. Parimala Devi, (Journal of Phytology, 2009)
Globally the usage of medicinal plants is increasing tremendously. By keeping this , we have made an attempt to list out the Indian medicinal plants which are highly useful in the treatment of viral infections and associated conditions. This may be helpful for the researchers who are working in the area of drug discovery from the herbal resources. Viral infections can be one of the biggest nightmares for medical doctors. And the use of antiviral herbs holds some distinct advantages over the use of drugs.